Beijing Treaty on Audiovisual Performances: Sudah Konsistenkah Hukum Indonesia Pasca Ratifikasi? - Andiani, Tia; Kusniati, Retno (Uti Possidetis: Journal of International Law, 2022)
This article discusses Indonesia's commitment to providing legal certainty for audiovisual performances in Indonesia. This article concludes that there is no consistency in Indonesian law in providing legal protection for audiovisual performances that have been ratified by Indonesia through Presidential Regulation No. 2 of 2020 on the international legal instruments of the Beijing Treaty. The issuance of Presidential Regulation Number 2 of 2020 does not necessarily provide legitimacy to apply these rules into Indonesian national law. Therefore, it is necessary to develop the law by establishing or changing copyright laws in accordance with the substance of the state's obligations in the Beijing Treaty for the protection of all parties involved in audiovisual performances.